Integrative Analysis of the lncRNA-Associated ceRNA Regulatory Network Response to Hypoxia in Alveolar Type II Epithelial Cells of Tibetan Pigs - Yang, Yanan; Li, Yongqing; Yuan, Haonan; Liu, Xuanbo; Ren, Yue; Gao, Caixia; Jiao, Ting; Cai, Yuan; Zhao, Shengguo (Frontiers in Veterinary Science, 2022)
The function of alveolar type II epithelial (ATII) cells is severely hampered by oxygen deficiency, and understanding the regulatory mechanisms controlling responses to hypoxia may assist in relieving injury induced by hypoxia. In this study, we cultured ATII cells from Tibetan pigs and Landrace pigs under hypoxic and normoxic environments to screen for differentially expressed (DE) lncRNAs, DEmiRNAs, and construct their associated ceRNA regulatory networks in response to hypoxia. Enrichment analysis revealed that target genes of DElncRNAs of Tibetan pigs and Landrace pig between the normoxic (TN, LN) and hypoxic (TL, LL) groups significantly enriched in the proteoglycans in cancer, renal cell carcinoma, and erbB signaling pathways, while the target genes of DEmiRNAs were significantly enriched in the axon guidance, focal adhesion, and mitogen-activated protein kinase (MAPK) signaling pathways. Hypoxia induction was shown to potentially promote apoptosis by activating the focal adhesion/PI3K-Akt/glycolysis pathway. The ssc-miR-20b/MSTRG.57127.1/ssc-miR-7-5p axis potentially played a vital role in alleviating hypoxic injury by regulating ATII cell autophagy under normoxic and hypoxic conditions. MSTRG.14861.4-miR-11971-z-CCDC12, the most affected axis, regulated numerous RNAs and may thus regulate ATII cell growth in Tibetan pigs under hypoxic conditions. The ACTA1/ssc-miR-30c-3p/MSTRG.23871.1 axis is key for limiting ATII cell injury and improving dysfunction and fibrosis mediated by oxidative stress in Landrace pigs. Our findings provide a deeper understanding of the lncRNA/miRNA/mRNA regulatory mechanisms of Tibetan pigs under hypoxic conditions.